2002
DOI: 10.1017/s095026880200777x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological consequences of a pathogen having both virulent and avirulent modes of transmission: the case of rabbit haemorrhagic disease virus

Abstract: A number of pathogens cause chronic infection in survivors of acute disease and this is believed to be a common means of persistence, including for highly virulent agents. We present a model in which transmission from chronically infected hosts causes chronic infection in naive individuals, without causing acute disease – indeed ‘protecting’ against it. Thus the pathogen obtains the benefit of virulence (high transmission rate), but mitigates against the cost (high host mortality). Recent findings suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…On the other hand, lower mortality rates due to non-RHD causes (White et al 2002) or higher production of offspring (Story et al 2004) have been suggested as compensatory mechanisms that may decrease the impact of RHD on populations. Moreover, Calvete (2006) developed a model showing that the impact of RHD can be highly dependent on rabbit population dynamics and, therefore, on habitat carrying capacity, and that the presence of a unique, highly pathogenic RHD virus can be compatible with the existence of high-density populations at equilibrium with the disease, without the concurrence of genetic variations among rabbit populations or the presence of a protective, non-pathogenic RHD-like virus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lower mortality rates due to non-RHD causes (White et al 2002) or higher production of offspring (Story et al 2004) have been suggested as compensatory mechanisms that may decrease the impact of RHD on populations. Moreover, Calvete (2006) developed a model showing that the impact of RHD can be highly dependent on rabbit population dynamics and, therefore, on habitat carrying capacity, and that the presence of a unique, highly pathogenic RHD virus can be compatible with the existence of high-density populations at equilibrium with the disease, without the concurrence of genetic variations among rabbit populations or the presence of a protective, non-pathogenic RHD-like virus.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors will affect infection outcome at the population level, such as strain virulence [9,33], herd immunity due to previous infections [4,34] population density, season of the year [7,35], anthropogenic changes in the environment [4], landscape [9] and viral transmission between populations [4,9,36].…”
Section: Citationmentioning
confidence: 99%
“…Moreover, White et al (2002;2004) have suggested that the same RHD virus might have both apathogenic and pathogenic effects, causing (1) an acute illness that, although very lethal, would allow the few survivors to produce antibodies, (2) Before the beginning the hunting season, we contacted those responsible of the hunting estates to finalize a date (ideally one) when rabbit samples could be collected: eye for age determination, and blood by cardiac puncture for serological study. We aimed to collect samples from 15-20 shot rabbits at each locality.…”
Section: Rabbit Hemorrhagic Diseasementioning
confidence: 99%